Potentially Inappropriate Prescribing in Older Patients Discharged From Acute Care Hospitals to Residential Aged Care Facilities. (November 2014) - Poudel, Arjun; Peel, Nancye M.; Nissen, Lisa; Mitchell, Charles; Gray, Len C.; Hubbard, Ruth E.
Background: The frequency of prescribing potentially inappropriate medications (PIMs) in older patients remains high despite evidence of adverse outcomes from their use. Little is known about whether admission to hospital has any effect on appropriateness of prescribing.Objectives: This study aimed to identify the prevalence and nature of PIMs and explore the association of risk factors for receiving a PIM.Methods: This was a prospective study of 206 patients discharged to residential aged care facilities from acute care. All patients were at least 70 years old and were admitted between July 2005 and May 2010; their admission and discharge medications were evaluated.Results: Mean patient age was 84.8 ± 6.7 years; the majority (57%) were older than 85 years, and mean (SD) Frailty Index was 0.42 (0.15). At least 1 PIM was identified in 112 (54.4%) patients on admission and 102 (49.5%) patients on discharge. Of all medications prescribed at admission (1728), 10.8% were PIMs, and at discharge, of 1759 medications, 9.6% were PIMs. Of the total 187 PIMs on admission, 56 (30%) were stopped and 131 were continued; 32 new PIMs were introduced. Of the potential risk factors considered, in-hospital cognitive decline and frailty status were the only significant predictors of PIMs.Conclusions: Although admission to hospital is an opportunity to review the indications for specific medications, a high prevalence of inappropriate drug use was observed. The only associations with PIM use were the frailty status and in-hospital cognitive decline. Additional studies are needed to further evaluate this association.